Exploring Sensory Attributes in Spinach- and Offals-Filled Chicken Roulades: An Empirical Analysis - Paul-Corneliu Boișteanu; Bianca-Georgiana Anchidin; Marius-Mihai Ciobanu (Foods)
One of the most significant industries in the world is the meat sector, and development into new goods is ongoing due to high customer demand and fierce market competition. Products made from chicken are widely favored. This phenomenon can be attributed to the lack of cultural or religious restrictions on this meat. The study looks into how using two distinct types of iron-rich fillings impacts the sensory profile of classic chicken roulades. The purpose of the study is to determine how changes in sensory qualities (such as taste, texture, and flavor) affect product acceptance among customers. This approach uses methods like check-all-that-apply (CATA), principal component analysis (PCA), external preference mapping (PrefMap), and penalty analysis to explore the impact of adding chicken offals and spinach as fillings on the sensory profile of traditional chicken meat roulades. This approach seeks to expand the meat product category, create new goods that use both plant and animal components, invent new ways to use offals and spinach in the market, and ensure that consumers accept these new products. Based on the results of our investigation, the type of filling utilized in the roulades showed the most differences across all sensory tests. According to hedonic analysis and preference mapping (PrefMap), the majority of customers favored roulades with spinach fillings as opposed to those containing chicken offals, which only a small portion of customers liked. Variations in consumer preference for roulades filled with chicken offals were noted in the anatomical region, with slightly greater preference for roulades made from chicken breast. However, this (anatomical region used) did not significantly affect the outcomes of all sensory tests. The spinach stuffing was found to be quite popular with the customers, even outperforming traditional chicken roulades, making it the most significant influence. Based on consumer appreciation, this suggests that the spinach-filled chicken roulades may be a viable option for meat products in the future.